Photomodulation of strigolactones in mediating sunflower seedling growth - Bharti, Niharika (The Scientific Temper, 2023)
Plants produce a large variety of non-proteinaceous biochemicals through primary and secondary metabolism. These compounds may act as signaling molecules, plant hormones, growth regulators (other than hormones) or as protectants from parasitic infections. In various attempts by scientists world over, a number of novel plant growth regulators have been discovered in the recent past. Over the past decade interesting information has been obtained on the biosynthesis, photomodulation and physiological roles of strigolactones (SLs) which are derived from carotenoid biosynthesis route. Adequate evidence is now available on their actions through transport to the target sites in the plant system. The regulatory roles of strigolactones have further been observed to be modulated by light in more than one ways. Present investigations report the photomodulation of strigolactones (SLs) in sunflower seedlings growth at their early developmental stages (2d, 4d, 6d). These observations indicate the migration of a probable light-sensitized signaling molecule (yet to be identified) or a SL precursor from light exposed aerial parts to the seedling roots maintained in dark. Thus, a photomodulation and migration of SL precursor/s is evident from the present work.